Utilization of urban sewage waters for irrigation of agricultural lands in Ukraine - Dyshlyuk, V. Ye. (Acta Agraria Debreceniensis, 2014)
The research results of ecological passportization for the municipal treatment facilities sewage disposals were presented (its chemical composition and sanitary measurements). There were determined the availability of the sewage disposals for irrigation and the prospects of use in agriculture.